2022
DOI: 10.1002/marc.202100891
|View full text |Cite
|
Sign up to set email alerts
|

Toughening Wet‐Spun Silk Fibers by Silk Nanofiber Templating

Abstract: Regenerated silk fibers typically fall short of silkworm cocoon fibers in mechanical properties due to reduced fiber crystal structure and alignment. One approach to address this has been to employ inorganic materials as reinforcing agents. The present study avoids the need for synthetic additives, demonstrating the first use of exfoliated silk nanofibers to control silk solution crystallization, resulting in all-silk pseudocomposite fibers with remarkable mechanical properties. Incorporating only 0.06 wt% sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…Specifically, the ultimate strength and Young’s modulus were both increased by about 20% after drawing ( Figure 5 b,c), and the breaking strain was largely improved from 0.05 to 0.5. 41 44 These two factors led to a substantial increase in toughness from ∼3 to 50 MJ m –3 ( Figure 5 d). We speculate that this improvement in mechanical properties may be attributed to changes in peptide conformation and/or orientation due to the drawing, 18 which will be further investigated in the next section.…”
Section: Resultsmentioning
confidence: 97%
“…Specifically, the ultimate strength and Young’s modulus were both increased by about 20% after drawing ( Figure 5 b,c), and the breaking strain was largely improved from 0.05 to 0.5. 41 44 These two factors led to a substantial increase in toughness from ∼3 to 50 MJ m –3 ( Figure 5 d). We speculate that this improvement in mechanical properties may be attributed to changes in peptide conformation and/or orientation due to the drawing, 18 which will be further investigated in the next section.…”
Section: Resultsmentioning
confidence: 97%
“…Recent reports showed that wet spinning can significantly improve the mechanical properties of RSF. [25][26][27] Meanwhile, the degree of aggregation of CeO 2 NPs can be reduced by stirring, and wet spinning can prevent the loss of nanomaterials over time. Compared with other preparation methods, wet spinning is more appropriate for prolonging the service life of RSF fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the surface modification method is not suitable for extending the service life of RSF fibers. Recent reports showed that wet spinning can significantly improve the mechanical properties of RSF 25–27 . Meanwhile, the degree of aggregation of CeO 2 NPs can be reduced by stirring, and wet spinning can prevent the loss of nanomaterials over time.…”
Section: Introductionmentioning
confidence: 99%
“…Natural silk fibers are biocompatible and biodegradable protein fibers and possess extraordinary mechanical properties due to their highly ordered hierarchical structure dominated by stable crystalline regions. [ 23 ] Natural silk fibers produced by Bombyx mori silkworms have been used traditionally as threads in luxurious textiles for more than 5000 years. Reliable mechanical performances ensure the functionality and durability of materials in diverse applications.…”
Section: Introductionmentioning
confidence: 99%
“…Wet‐spun fibers with SNFs showed remarkably enhanced tensile strength and toughness compared to pure regenerated silk fibers. [ 23 ] Moreover, the combination of SNFs into CS composites could enhance cell attachment. [ 29 ] CS/SNFs composite films prepared by formic acid/calcium chloride solvent system had high strength and elasticity, and showed the potential to regulate cell behaviors.…”
Section: Introductionmentioning
confidence: 99%